Modulation of the IL-6-Signaling Pathway in Liver Cells by miRNAs Targeting gp130, JAK1, and/or STAT3 - Florence A. Servais; Mélanie Kirchmeyer; Matthias Hamdorf; Nadège W.E. Minoungou; Stefan Rose-John; Stephanie Kreis; Claude Haan; Iris Behrmann (Elsevier, 2019)
Interleukin-6 (IL-6)-type cytokines share the common receptor glycoprotein 130 (gp130), which activates a signaling cascade involving Janus kinases (JAKs) and signal transducer and activator of transcription (STAT) transcription factors. IL-6 and/or its signaling pathway is often deregulated in diseases, such as chronic liver diseases and cancer. Thus, the identification of compounds inhibiting this pathway is of interest for future targeted therapies. We established novel cellular screening systems based on a STAT-responsive reporter gene (Cypridina luciferase). Of a library containing 538 microRNA (miRNA) mimics, several miRNAs affected hyper-IL-6-induced luciferase activities. When focusing on candidate miRNAs specifically targeting 3' UTRs of signaling molecules of this pathway, we identified, e.g., miR-3677-5p as a novel miRNA affecting protein expression of both STAT3 and JAK1, whereas miR-16-1-3p, miR-4473, and miR-520f-3p reduced gp130 surface expression. Interestingly, combination treatment with 2 or 3 miRNAs targeting gp130 or different signaling molecules of the pathway did not increase the inhibitory effects on phospho-STAT3 levels and STAT3 target gene expression compared to treatment with single mimics. Taken together, we identified a set of miRNAs of potential therapeutic value for cancer and inflammatory diseases, which directly target the expression of molecules within the IL-6-signaling pathway and can dampen inflammatory signal transduction. Keywords: microRNAs, signal transduction, interleukin-6, gp130, cytokine, JAK1, STAT3, cancer, inflammation, liver